Strengthening the Local Economy Through Empowering Shrimp Production (Product Packaging Design Ideas) - Arlina, Arlina; Prayoga, Hafizh; Hamdani, Hamdani; Lubis, Syifa Aramitha; Andika, Luthfie Budie (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
UKM (Small and Medium Enterprise-based Terrace) is one of the efforts that plays an important role in the development of the local economy. Especially in the coastal areas of Ivory Coast Village. kecepe shrimp, as the main raw material, have high economic value and large market potential because it is used in various traditional cuisines. . In addition, unique and interesting packaging designs are also one of the attractiveness and innovations for these porch products. The purpose of this study is; a). To find out the materials and process of making shrimp paste kecepe, and b) products. To provide new packaging design innovation. The research method used in this study is descriptive qualitative, with the type of research method, namely the fenomenologis study with the intention of observing and seeing the data directly and the suitability of the situation that occurs. Data collection techniques are carried out with interviews, observations and documentation. The data sources used are primary data, with research subjects, namely home industry players on the porchi and research objects, namely local shrimp products. The data analysis used is data reduction, data presentation and drawing conclusions. The results show that the ingredients and process of making terraces consisting of kecepe shrimp, water and rough salts through the preparation stages of kecepe shrimp, washing, drying, kissing, fermmentasi and printing and packaging. The results also show that compelling and unique packaging designs can increase sales and avoid product claims by irresponsible parties.